1969
DOI: 10.2134/agronj1969.00021962006100060009x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Sugar Beets as Affected by Root Temperatures Part I: Greenhouse Studies1

Abstract: Sugar beets (Beta vulgaris var. saccharifera) were grown in the greenhouse at 10 different constant root temperatures. The temperature intervals were maintained at 2.8 C between 12.8 and 37.8 C. Optimum root temperature for sugar beet emergence occurred in the range of 25–35 C. The optimum root temperature for dry matter production in sugar beet tops progressively decreased from 26.3 C at 6 weeks following emergence to 23C at 13 weeks following emergence. Optimum temperatures for sugar beet roots remained betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Another important change was the modification of the base and upper temperature (Table 2) for better simulation of the crop development and the impact of low temperatures on stomatal conductance [29]. Our proposed changes are in line with those recommended by Reference [37] for the base temperature and by References [38] and [39] for the upper temperature. Although the default crop water stress parameters (Table 2) satisfactorily simulated the crop response under deficit irrigation (Figure 1b-d, Figures 2b-d and 3), a small change in the parameter that adjust HIo for water stress during yield formation (Table 2) allowed the correct simulation of the increase in HI due to the water stress suffered during the leaf expansion, as observed by Reference [40].…”
Section: Discussionmentioning
confidence: 58%
“…Another important change was the modification of the base and upper temperature (Table 2) for better simulation of the crop development and the impact of low temperatures on stomatal conductance [29]. Our proposed changes are in line with those recommended by Reference [37] for the base temperature and by References [38] and [39] for the upper temperature. Although the default crop water stress parameters (Table 2) satisfactorily simulated the crop response under deficit irrigation (Figure 1b-d, Figures 2b-d and 3), a small change in the parameter that adjust HIo for water stress during yield formation (Table 2) allowed the correct simulation of the increase in HI due to the water stress suffered during the leaf expansion, as observed by Reference [40].…”
Section: Discussionmentioning
confidence: 58%
“…Cystosori were found in less than 8% of lateral roots per sample during the 28 days of the experiment and their density was always considerably less than in plants grown at 15 C. Reduced fungal development at this high temperature could be due. in part at least, to the effect of temperature on plant growth, the optimum for sugar beet being 23 25 C (Radke & Bauer, 1969). Changes in root metabolism and exudation associated with these above optimum temperatures could affect cyst germination, zoospore attraction or encystment.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen and Tadmor (1969) observed that root elongation of grass and legume seedlings increased with increasing temperature from 10 to 20C, but varied among species from 20 to 25C. Radke and Bauer (1969) reported that optimum root temperature for dry matter accumulation by sugar beet (Beta saccharifera) roots was 24 to 25C while percent sucrose increased with increasing root temperatures from 19 to 32C.…”
mentioning
confidence: 99%